Food standards: Modeling regulatory changes in trade impact assessments. Simulations with an extended structuralist computable general equilibrium (CGE) model - Rudiger Von Arnim; Bernhard Tröster; Werner Raza (Hans-Böckler-Stiftung, 2024)
Is the harmonization of different food standards between countries in the context of free trade agreements exclusively positive, or is there a risk of high social costs for consumers? The harmonization of different national regulations plays an important role in contemporary trade policy. In this paper, the costs and benefits of harmonizing food safety regulations between the EU and the USA are estimated, using the ÖFSE Global Trade Model. The results show that the cost savings for companies due to the harmonization of regulatory standards are significantly lower than the associated negative effects on public health. Trade policy impact assessments must therefore take into account the social costs of regulation. – – Ist die Angleichung unterschiedlicher Lebensmittelstandards zwischen Ländern im Kontext von Freihandelsabkommen ausschließlich positiv zu bewerten, oder besteht hier die Gefahr von Qualitätsverlusten mit hohen sozialen Kosten für die betroffene Bevölkerung? Die Angleichung unterschiedlicher nationaler Regulierungen spielt in der zeitgenössischen Handelspolitik eine wichtige Rolle. In diesem Working Paper werden die Kosten und Nutzen der Angleichung von Lebensmittelsicherheitsvorschriften zwischen der EU und den USA mithilfe des "ÖFSE Global Trade Model" exemplarisch abgeschätzt. Die Ergebnisse zeigen, dass die Kostenersparnisse für Unternehmen aufgrund der Angleichung regulatorischer Standards deutlich geringer ausfallen als die damit einhergehenden negativen Effekte auf die öffentliche Gesundheit. Die handelspolitische Folgenabschätzung muss daher die gesellschaftlichen Kosten regulatorischer Qualitätsverluste systematisch berücksichtigen.
Keywords: 330; non-tariff barriers; TTIP; CETA; free-trade agreements; global markets